Mastite clínica em fêmea bovina - Lopes, Paula Lorhanna Barbosa (Universidade Federal do Tocantins, 2022)
The activities constituting the mandatory curricular supervised internship in Veterinary Medicine were developed in the city of Brejo Grande do Araguaia-PA, in the areas of Animal Reproduction and Veterinary Medical and Surgical Clinics, from January 19 to April 1, 2021, totaling 416 hours, under the supervision of the Veterinarian Rodrigo Rodrigues Assis and orientation of Prof. Dr. Katyane de Sousa Almeida. This report contains the description of the internship site, the casuistry, and follow-up of the activities developed during the routine of the veterinarian. Initially, the internship took place during the performance of activities inherent to the medical clinic for large animals and occurred due to the routine of the veterinarian when performing care in the surrounding properties, and later some cases ended up needing more attention and surgical interventions performed in the field. Throughout the internship, animals were followed for implementation of IATF protocol, followed by cyclicity evaluations and gynecological evaluation in females for initiation. This report also contains a case report of clinical mastitis in a female bovine, in which the patient was treated and submitted to drug therapy.